Federal Home Loan Bank advances and small business lending - Travis R. Davidson; W. Gary Simpson (The Journal of Entrepreneurial Finance (JEF), 2016)
Adequate credit availability for small businesses is an important public policy issue because small businesses are essential for employment and economic growth for the economy. The Gramm-Leach-Bliley Act of 1999 includes a provision that could potentially support financial institutions in the provision of credit to small businesses through the use of advances from the Federal Home Loan Bank (FHLB) system that are secured with small business loans. We explore the relation between FHLB advances to financial institutions and the provision of loans to small businesses. We find a positive link between the change in FHLB advances and the change in small business loans and the level of FHLB advances and the level of small business loans. This relation holds for large and small banks and pre- and post-2007 recession. However, we find that the change in the proportion of small business loans to assets is only positively related to the change in the advances to assets ratio prior to the recessionary period. This suggests that banks substitute small business loans for other types of assets during relatively normal economic periods, but FHLB advances are a source of wholesale funds that will be invested in the most attractive financial assets available with no preference for any particular asset during periods of contracting credit.
Keywords: G21; G28; 650; Federal Home Loan Bank; Advances; Small Business Lending; Small Business Credit